Pengaruh Ukuran Perusahaan, Komite Audit, Dan Integritas Laporan Keuangan Terhadap Kualitas Audit Pada Perusahaan Sub Sektor Makanan Dan Minuman Yang Terdaftar Di BEI - Raihan Akbar; Hermi Hermi (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2024)
The purpose of this study is to investigate the reciprocal interactions among firm size, audit committee, financial statement integrity, and audit quality. The research focuses on all companies operating in the food and beverage subsector listed on the Indonesia Stock Exchange (IDX) during the period from 2018 to 2022. Data was collected using purposive sampling, selecting 100 companies that met specific criteria during this period. Secondary data were obtained from sustainability reports and annual reports of the companies. The study employs a quantitative analysis approach, where data is analyzed through logistic regression using SPSS software version 23. Through this method, the research aims to explore the joint consequences of these variables, forming a deeper understanding of the dynamics and interactions among company size, audit committee, financial statement integrity, and audit quality in the context of the food and beverage subsector on the Indonesia Stock Exchange during the study period. Based on the research findings, it can be concluded that there is a significant positive relationship between firm size and financial statement integrity with audit quality. However, the results indicate that the audit committee does not have a significant impact on audit quality.